Study of Right Marginal Artery in Post Mortem Hearts of Adult Bangladeshi People - Hossain, A; Ara, A; Ara, S (Cardiovascular Journal, 2011)
Background: Heart disease is one of the major public health problems in Bangladesh. Treatment of heart disease is costly & complex issue. The study of anatomy of the right marginal artery is essential for the proper diagnosis and treatment of the heart diseases. Materials: The study was carried out in the Department of Anatomy, Dhaka Medical College (DMC), Dhaka from February 2005 to January 2006. Post mortem study of sixty (60) adult human hearts of Bangladeshi people aging from 20 to 75 years was performed. The samples were divided into 3 age groups – Group A (20 to 40 years) consists of 35 males & 7 female, Group B (41 to 60 years) consists of 8 male & 3 female and Group C (61 to 75 years) consists of 7 male. All the samples of different age groups were examined morphologically. Results: In the present study, the right marginal artery was present in 54 and absent in 6, out of 60 samples. Out of 54, the right marginal artery was terminated at the apex in 15 and nearer to the apex in 39 cases. Conclusion: The result of the present study can be helpful to the cardiologists and cardiovascular surgeons for proper anatomical assessment of coronary arteries in patients with heart diseases Key words: Postmortem heart; Coronary arteries; Right marginal artery. DOI: http://dx.doi.org/10.3329/cardio.v1i2.8123 Cardiovasc. j. 2009; 1(2) : 165-168